Trabalho social com famílias no cotidiano dos assistentes sociais e psicólogos a partir de demandas em unidades do Cras - Passaura, Lourdes (2018)
The purpose of this thesis is the work with families carried out from daily actions of social workers and psychologists in units of the Social Assistance Reference Center (CRAS). Its objectives are the study and analysis of the relation of theory in the movement of approximation of this work; dialogue on the contributions and difficulties of these professionals; the view of interdisciplinarity in the interface between Social Work and Psychology, including divergences and results. The methodology included theoretical studies and qualitative, descriptive and analytical research, based on the theoretical-methodological framework of historical-dialectical materialism. The technique used was that of the focal group, which had as one of the criteria the choice of people who share the same place of work; the reports / experiences; the necessities; the values; meanings; challenges; and elements of the chosen theme. The study included the participation of four psychologists and six social workers, professionals from three different CRAS units from Lins/SP city. The participatory methodology, through the collection of information obtained from the respondents, aimed to know and analyze social work with families in the daily life of social workers and psychologists in CRAS units; to redeem the conceptions, meanings, perspectives, divergences, conclusions and challenges identified in the intervention. The results point to the need to overcome the family tendency in inclusion in social policy. In this sense, it is considered necessary the exercise of a preventive social policy and of investment, that promote the right to the familiar coexistence, aspect pointed out by the members of the research, for improvements in relation to the effective vigilance; interdisciplinary teamwork (networking); the systematic, organized, continuous and joint attendance to the families, considering the diagnosis of the territory; the training and updating that promote professional clarity and autonomy, with the guarantee of sufficient technical staff. The final considerations include the challenges and the need to strengthen the coexistence services, as a priority, the home service for the elderly; the achievement of established goals by the social policy, a clear guideline in the methodological procedure within the services for the management work in the CRAS units; and conceptual innovations about family and social policy